AKIBAT HUKUM TERHADAP KELAHIRAN ANAK DARI PERKAWINAN YANG TIDAK TERCATAT BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Herina, Perida (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTPerida Herina, 2019, Legal consequences of the birth of unmarried children from marriage bassed on Law Number 1 of 1974 concerming marriage, This study was guided by Dr. H. Abdul Rokhim, S.H., M.Hum as the first supervisor and Gusti Heliana Safitri, S.H., M.H as supervisor II.Marriage is an inner and outer bond between a man and woman as husband and wife with the aim of forming a happy and eternal family bassed on the one godhead, carried out according to their respective Religion must be recorded according to the applicable laws and regulations.Research Methods, namely: 1. Type of Research, is Normative Juridical research. 2. Through the stages 3. Legal Material Resources, the author uses the technique of collecting library research, which in 4. Legal collection and processing materials using the primary law legal document collection techniques, as well as the implementing regulations of the Civil Code, Law No.23 of 2002 Law No. 23 of 2006, Law No. 1 of 1974, Presendential Degree No. 12 of 1983. b. Legal Materials The principal of the law is an approach to the problem, is the primary and Secondary Legal Materials Secondary data, sourced from: a. Material in 2002. Law No. 23 of 2006, Law No. 1 of 1974, Presidential Decree No. 12 0f 1983, b. Secondary Legal Materials books, internet access witings of legal experts, primary and secondary.c. Tertiary Law, namely givingnan explaination of primary law and seondary. 5. Legal Materials Analysis is that the data obtained is processed systematically, analyzed qualitatively, legal and analogical interpretations of the facts obtained by the study of provisions of the marriage.MK Decision Number:46/ PUU-VIII/2010 namely Children born proven based on science and technology and / or other evidence according to the Law has blood relations including the relationship of civil blood to his father’s familiy.